Left‐liver hypertrophy after therapeutic right‐liver radioembolization is substantial but less than after portal vein embolization. Issue 5 (1st April 2014) - Garlipp, Benjamin; de, Thierry; Damm, Robert; Irmscher, Romy; van, Mark; Stübs, Patrick; Deschamps, Frederic; Meyer, Frank; Seidensticker, Ricarda; Mohnike, Konrad; Pech, Maciej; Amthauer, Holger; et al.
<x xml:space="preserve">Abstract</x> In patients with liver malignancies potentially amenable to curative extended right hepatectomy but insufficient size of the future liver remnant (FLR), portal vein embolization (PVE) of the tumor‐bearing liver is used to induce contralateral liver hypertrophy but leaves the tumor untreated. Radioembolization (RE) treats the tumor in the embolized lobe along with contralateral hypertrophy induction. We performed a matched‐pair analysis to compare the capacity for hypertrophy induction of these two modalities. Patients with right‐hepatic secondary liver malignancies with no or negligible left‐hepatic tumor involvement who were treated by right‐lobar PVE (n = 141) or RE (n = 35) at two centers were matched for criteria known to influence liver regeneration following PVE: 1) baseline FLR/Total liver volume ratio (<25 versus ≥25%); 2) prior platinum‐containing systemic chemotherapy; 3) embolization of segments 5‐8 versus 4‐8; and 4) baseline platelet count (<200 versus ≥200 Gpt/L).The primary endpoint was relative change in FLR volume from baseline to follow‐up. Twenty‐six matched pairs were identified. FLR volume increase from baseline to follow‐up (median 33 [24‐56] days after PVE or 46 [27‐79] days after RE) was significant in both groups but PVE produced significantly more FLR hypertrophy than RE (61.5 versus 29%, P < 0.001). Time between treatment and follow‐up was not correlated with the degree of contralateral hypertrophy achieved in both groups. Although group differences in patient history and treatment setting were present and some bias cannot be excluded, this was minimized by the matched‐pair design, as remaining group differences after matching were found to have no significant influence on contralateral hypertrophy development. Conclusion: PVE induces significantly more contralateral hypertrophy than RE with therapeutic (nonlobectomy) doses. However, contralateral hypertrophy induced by RE is substantial and RE minimizes the risk of tumor progression in the treated lobe, possibly making it a suitable modality for selected patients. (Hepatology 2014;59:1864–1873)